Delineation of the clinical profile of CNOT2 haploinsufficiency and overview of the IDNADFS phenotype. Issue 2 (24th November 2022) - Niceta, Marcello; Pizzi, Simone; Inzana, Francesca; Peron, Angela; Bakhtiari, Somayeh; Nizon, Mathilde; Levy, Jonathan; Mancini, Cecilia; Cogné, Benjamin; Radio, Francesca Clementina; Agolini, Emanuele; Cocciadiferro, Dario; et al.
Abstract: CNOT2 haploinsufficiency underlies a rare neurodevelopmental disorder named Intellectual Developmental disorder with NAsal speech, Dysmorphic Facies, and variable Skeletal anomalies (IDNADFS, OMIM 618608). The condition clinically overlaps with chromosome 12q15 deletion syndrome, suggesting a major contribution of CNOT2 haploinsufficiency to the latter. CNOT2 is a member of the CCR4‐NOT complex, which is a master regulator of multiple cellular processes, including gene expression, RNA deadenylation, and protein ubiquitination. To date, less than 20 pathogenic 12q15 microdeletions encompassing CNOT2, together with a single truncating variant of the gene, and two large intragenic deletions have been reported. Due to the small number of affected subjects described so far, the clinical profile of IDNADFS has not been fully delineated. Here we report five unrelated individuals, three of which carrying de novo intragenic CNOT2 variants, one presenting with a multiexon intragenic deletion, and an additional case of 12q15 microdeletion syndrome. Finally, we assess the features of IDNADFS by reviewing published and present affected individuals and reevaluate the clinical phenotype of this neurodevelopmental disorder. Abstract :